Metallurgical bond integrity of C45 ultra fine pitch with 18m copper wire - Kid W.B.; Leng E.P.; Seong L.B.; Weily C.; Kar Y.B. (2023)
Nowadays, increasing of gold price and decreasing of dielectric let copper and low-k dielectric materials become a new technology and are increasingly chosen as preferred interconnect insulated material in semiconductor applications. In this paper, a C45 ultra low k wafer technology with bond-over-active bond pads, on a thermally enhanced BGA package with 3131mm large body size is selected to study. Aluminum wire type, bonding capillary, and wire bonding parameters, were selected as critical factors in this study. Both were used for bonding parameters optimization. Critical responses such as ball size, ball height/bonded ball diameter ratio, wire pull strength, ball shear strength, and wire peel strength were studied to understand the wire bonding effect of C45 ultra low k and 40m pad pitch. Analysis between copper and gold wire were performed for comparison purpose at different thermal aging read point. The thermal aging read point were studied at 175C for 168, 504 and 1008 hours while at temperature of 225C for 4.5, 13.5, 26, 52 and 97 hours respectively. This is used to study the IMC thickness of Cu-Al. To investigate the effects of IMC formation on the copper wire on Al pad, wire pull, wire peel and ball shear test has to be construct. 2011 IEEE.